Public and Private in Ancient Mediterranean Law and Religion - Ando, Clifford; R©ơpke, J©œrg (Religionsgeschichtliche Versuche und Vorarbeiten, 2015)
"The public/private distinction is fundamental to modern theories of the family, religion and religious freedom, and state power, yet it has different salience, and is understood differently, from place to place and time to time. The volume examines the public/private distinction in the cultures and religions of the ancient Mediterranean, in the formative periods of Greece and Rome and the religions of Judaism, Christianity and Islam"--